Iodine Redox-Mediated Electrolysis for Energy-Efficient Chlorine Regeneration from Gaseous HCl. Issue 7 (1st January 2017) - Zhao, Yun; Gu, Shuang; Gong, Ke; Zheng, Jie; Wang, Junhua; Yan, Yushan
Abstract : Hydrogen chloride (HCl) by-product is often produced from chlorine-consuming processes. Traditional electrochemical processes for converting HCl to chlorine (Cl2 ) are completed by anodic oxidation reaction coupled with cathodic reduction reactions (two major types: hydrogen evolution reaction and oxygen reduction reaction). Herein, a triiodide (I3 − )/iodide (I − ) redox-mediated cathode is implemented for the first time for converting HCl to Cl2 . The iodide (I − ) can be converted back to triiodide (I3 − ) by air in a reactor external to the eletrolyzer. The desirable redox potential and facile kinetics of I3 − /I − offer a substantially lower operational cell voltage, reducing energy consumption by 20%–25% at a typical current density of 4 kA m −2 and improving the efficiency of Cl2 recovery.